2018
DOI: 10.1097/pec.0000000000001565
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Behavioral Health Patients on a Pediatric Emergency Department's Length of Stay and Left Without Being Seen

Abstract: Behavioral health census and bed hold hours were significantly associated with increased LOS and LWBS rates and with our inability to meet desired LOS and LWBS rates. These associations support the existence of a threshold where the ED has reached capacity and is no longer able to absorb BH patients. Improving BH facility access may help improve overall pediatric ED patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…MH presentations can strain already limited ED resources, this cohort is more likely to have recurrent ED presentations, 15,16 require an extended length of stay (LOS) and are more likely to need admission than children who present with a physical diagnosis 6,8,10,11 . Results from a recent Australian study had similar findings and also found that 22.5% of all paediatric MH presentations were for self‐harm 12 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 74%
See 1 more Smart Citation
“…MH presentations can strain already limited ED resources, this cohort is more likely to have recurrent ED presentations, 15,16 require an extended length of stay (LOS) and are more likely to need admission than children who present with a physical diagnosis 6,8,10,11 . Results from a recent Australian study had similar findings and also found that 22.5% of all paediatric MH presentations were for self‐harm 12 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 74%
“…Australian emergency departments (EDs) are seeing an alarming increase in MH presentations across all ages with the most rapid increases in the paediatric population 4,5 . This trend is consistent globally and has been well studied in North America 6–11 . However in Australia, paediatric‐specific studies are limited 12–14 …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…First, the number of patients presenting with a MHD in paediatric EDs correlates with a longer ED-LOS for all other patients, and a higher rate of leftbefore-being-seen for the entire ED cohort. 3 For older patients with MHDs, an ED-LOS longer than 8 h carries a one in eight chance of developing an episode of delirium. 6 Long waits for patients with MHDs awaiting admission is a factor in overcrowding, 5,7 and correlates with poorer outcomes for staff, systems and patients alike.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, older patients with MHDs waited 48 min longer in ED than older patients without MHDs 2 . In the USA, this phenomenon appears to be of greater magnitude: patients waiting for a psychiatric bed in the USA have been found to wait between 5 and 12 h longer, depending on the study 3,4 . The ED patient journey is also different for patients with a MHD, and delays can occur at various timepoints unique to this population (Box 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation